Public attitudes towards KRG Public Relations - Bali, ASST. Prof. Dr. Ahmed Omer; Kareem, L. Tazhan Dlshad (Sulaimani Journal for Humanities, 2024)
Government Public Relations, also known as government relations or public affairs, is all about creating and maintaining positive relationships with the public. The public's perceptions of official data offerings, the operations of public utilities, and the connection between public knowledge and service delivery are all examined in this research. In order to learn more about the public's views regarding providing data and services supplied by public utilities, as well as the relationship between knowledge and government services, the present research used a survey method. It recruited participants from people of all ages in Iraqi Kurdistan who were 25 years of age and older using a web-based survey made with Google Forms (N 622). According to this research, publicity campaigns launched by government institutions do not adequately supply the data required to resolve public issues. Everyone is badly impacted by this ignorance. This study found an association between public attitude toward government information and KRG public policy. Hence, this study recommends that the KRG develop its communication, in addition to informing reforms in its policy and capacity building.
Keywords: Public Relations; Government; KRG; Public Value; System Theory